مدى استخدام مفهومي تحليلات البيانات الضخمة وحوكمة تكنولوجيا المعلومات ودورهما في كشف الغش بالقوائم المالية: دراسة ميدانية على المصارف التجارية (Comprehensive Journal of Science, 2025)
This research aims to measure the extent of use of the concepts of big data analytics and information technology governance and their role in detecting fraud in financial statements by applying them to commercial banks during the period from 2025, especially in the existence of a guide for applying information technology governance issued by the Central Bank of Libya, as the results of the research showed: the lack of use of the concept of big data analytics in commercial banks, the lack of use of the concept of information technology governance in Libyan commercial banks, Finally, while traditional tools are effective in detecting fraud in financial statements of Libyan commercial banks, they offer limited benefits due to rapid developments and changes. Modern financial and non-financial tools, such as big data analytics and information technology governance, can significantly enhance the ability to confront and reduce fraud risks.
Keywords: Big Data Analytics - Information Technology Governance - Detecting Fraud in Financial Statements.